Correlation of Characteristics and Nutritional Status on Length Of Stay of ICU Patients in Purwakarta - Faris Amri (Universitas Pendidikan Indonesia, 2020)
Length of stay shows the level of management efficiency and quality of care provided by the hospital. The length of stay from the economic aspect for the patient will increase the cost of care that they have to pay. Characteristics, nosocomial infections, complications, and wound healing can affect the patients' length of stay. This study aims to analyze the correlation between characteristics and nutritional status with the length of stay of ICU patients in Purwakarta. This study is a quantitative analytical study using secondary data, namely the patient's medical record. The accidental sampling technique selected a total of 80 patient data in this study. The variables studied were gender, age, occupation, type of diagnosis, nutritional status, and length of stay. Data were analyzed using chi-square. The results of the analysis using the Chi-square test showed that there were three variables related to the length of stay of ICU patients, namely age (p = 0.040), type of disease (p = 0.005), and nutritional status (p = 0.047). Gender (p=0.96) and occupation (p=0.234) were not related to the length of stay of ICU patients. Age, type of diagnosis, and nutritional status related to the length of stay of ICU patients. Hospitals need to provide exceptional services to elderly and malnourished patients to speed up the healing process.